Micro Electro-Fabrication - Saleh, Tanveer (Elsevier, 2021)
Electro-machining is an emerging technology used for microengineering. There are various types of such technologies, which researchers are currently investigating, such as electro-discharge machining (EDM), electro-chemical machining (EMM), electrochemical discharge machining (ECDM), etc. EDM is essentially an electro-thermal process where the material is being removed from the workpiece by repetitive sparks between the tool and workpiece. Electro-chemical machining, on the other hand, uses anodic dissolution principle to carry out the machining. Electro-chemical discharge machining is basically a hybrid process combining EDM and EMM into a single process to achieve better accuracy on the finished product. Application of electro-machining techniques is vast. Some of these applications include fabrication of nozzles for automobiles, miniature hole machining for aerospace turbine blade cooling, biomedical device fabrication such as stents, fabrication of microchannels for microfluidic application and production of various MEMS devices, rapid prototyping of microcomponents and nanoelectrode fabrication for scanning electron microscopy. A comprehensive understanding of various types of Electro-machining techniques is needed for the effective uses of such technology. Therefore, currently, there is a need for a single book which can accommodate elaborate discussions on varieties of electro-machining methods. This book is aiming to address this need. This book discusses about the nature of different electro-machining processes as well as their applications. This book can be used as reference material for researchers and postgraduate students as well as industry players who intend to work in the field of electro-machining for microfabrication. Chapter 1, Electro-Spark Process for Microfabrication, of this book discusses on Electro-discharge micromachining which is a variant of Electro-machining. The chapter elaborated on the process description, system requirement for the process, parametric analysis of the process, various types of Electro-Discharge micromachining, and finally concluded by discussing about the pros and cons of the said process. Chapter 2, Microfabrication by EDM-based Hybrid Processes, discusses on microfabrication using EDM-based hybrid process. Some of the hybrid EDM processes that are highlighted are vibration-assisted EDM, Laser-assisted EDM, Magnetic fieldassisted EDM, and abrasive-assisted EDM. Chapter 3, Trends in EDM of Ti and Ni-based Superalloys: Macro-Micro- Compound Arc/Spark/Melt Process, explores application of EDM on a special material titanium- and nickel-based superalloys. This chapter presents the compounding of EDM with different arcing/sparking/melting processes, along with detailed working principles and examples. Performance of these processes is also discussed evaluated in terms of multifarious criteria such as surface integrity, material removal rate, electrode wear ratio, machining time, precision dimension, etc. Chapter 4, Batch Mode Microelectro-discharge Machining, on the other hand, describes how EDM technology can be used for batch mode microfabrication. The chapter also demonstrates the application of batch mode EDM for fabricating high aspect ratio copper electrode array and various shaped microholes array. Tool wear is a drawback for EDM technology which causes inaccuracy in the final product if not compensated properly. Chapter 5, Wear Compensation in Electrodischarge Machining Process Using Adaptive Neuro Fuzzy Inference System, presents a method of tool wear compensation in EDM by using Adaptive Neuro Fuzzy technique. The proposed technique has been found to be effective in compensating tool wear for EDM-based microfabrication. Chapter 6, Surface Modification of High-performance Alloys Through Micro-EDM Processes, elaborates on how a workpiece surface is modified as the EDM process is conducted. This chapter provided a detailed study on the different EDM/micro-EDM techniques used for surface modification such as by proper selection of tool electrode or dielectric medium, powder mixed dielectric, green compact electrodes, sintered electrodes, etc. Chapter 7, Strategies of Improving Accuracy in Micro-EDM, studied various strategies on improving the micro-EDM accuracy. Some of the sources of inaccuracy that authors highlighted in the chapter are stochastic nature of the process, handling of the microelectrode, wobbling and vibration of the tool, and tool wear, etc. They also describe various processes to mitigate these sources. Shape memory alloy actuator (SMA) is a widely used material in the field of MEMS. Chapter 8, Electrical Discharge Machining for the Fabrication of Bulk-Shape Memory Alloy Microactuators, discusses how EDM can be used to fabricate bulk SMA actuators. They studied various SMA actuators that can be fabricated using EDM such as micromanipulator, micropositioning stage and tunable coil, etc. Silicon is a semiconductor material that has been used as workpiece material for micro-EDM research by several researchers. Chapter 9, Silicon Micromachining Using Electrical Discharge Method, consolidates these researches into a single chapter. Chapter 10, Performance Enhancement of Microelectrical Discharge Machining Using Powder Additives Mixed Dielectrics, describes an interesting phenomenon on using powder additives to improve the micro-EDM performance. Upon addition of powder (conductive as well as semiconductive) can influence the process capabilities and may result in the enhanced EDM stability. EDM is mostly applied for conductive material. Chapter 11, Microelectrochemical Sparks Machining: A Modern Approach for Fabrication of Microcomponents from Nonconductive Materials, investigated a novel method of machining nonconductive materials using electro-chemical spark machining (ECSM). This chapter also outlines the various material machined by micro-ECSM process and the enhancements of the machining potential by its hybrid variant and provides new prospect in technological advancement of micro-ECSM process. Chapter 12, Electro-chemical Discharge Machining: Trends and Development, describes elaborately the recent trends and developments of ECDM. Various forms of this process such as ECDM turning, ECMD milling, and ECDM grinding will be presented in this chapter. Chapter 13, Electrochemical Machining for Microfabrication, discusses the technology of electro-chemical machining for microfabrication. Unlike EDM electro-chemical machining is free from tool wear, which makes it somewhat advantageous over EDM. This chapter describes various aspects of electro-chemical machining. The editors acknowledge Elsevier for this opportunity and their professional support. The editors would also like to acknowledge the authors of book chapters for their significant effort to contribute to this book.